Sports-related wrist and hand injuries: a review. Issue 1 (December 2016) - Avery, Daniel; Rodner, Craig; Edgar, Cory
Abstract Background Hand and wrist injuries are common during athletics and can have a significant impact especially if initially disregarded. Due to their high level of physical demand, athletes represent a unique subset of the population. Main body The following is an overview of hand and wrist injuries commonly seen in athletics. Information regarding evaluation, diagnosis, conservative measures, and surgical treatment are provided. Conclusion Knowledge of these entities and special consideration for the athlete can help the team physician effectively treat these players and help them achieve their goals.